Polymorphisms of Tumor Necrosis Factor-α, Transforming Growth Factor-β, and Interleukin-10 in Asthma Associated with Olive Pollen Sensitization - Blanca Cárdaba; David Calzada; Selene Baos; Miriam Aguerri; Joaquín Quiralte; Carlos Lahoz (Journal of Immunology Research)
Sensitization to specific olive pollen-allergens (Ole e 2 and 10) has been correlated with a clinical pattern of asthma. This study analyzes the association between several polymorphims of TNFA (G-308A, C-857T, and C-1031T), IL10 (C-571A and A-1117G), and TGFB (C-509-T) and these sensitizations. These polymorphisms were genotyped by allelic discrimination, in olive pollen-allergic patients (phenotyped for specific Ole e 2 and 10 sensitizations) and healthy controls. Levels of serum-soluble cytokines were correlated with specific genotypes and clinical phenotypes. The results showed that heterozygous TGFB C-509T genotype, besides having the lowest sera TGF- levels, was significantly increased in olive pollen-allergic patients compared with controls. According specific sensitizations, CC genotype of IL10 C-571A could be a protective factor for Ole e 2 sensitization and mainly for asthmatic Ole e 2 sensitized patients compared with asthmatic non-Ole e 2 sensitized patients (OR: 0.26, P=0.008). In contrast, heterozygous CA genotype was increased in Ole e 2 asthmatic subjects compared to asthmatic non-Ole e 2 sensitized patients. Lastly, heterozygous TNFA G-308A genotype was associated with Ole e 10 sensitization (OR: 2.5, P=0.04). In conclusion, these results suggest a role of TGF-β1 in olive-pollen sensitization and TNF-α and IL-10 genotypes in the asthma induced by specific olive-pollen allergens.